2004
DOI: 10.1108/01435120410533756
|View full text |Cite
|
Sign up to set email alerts
|

OAI compliant institutional repositories and the role of library staff

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 3 publications
0
30
0
2
Order By: Relevance
“…Academic library staff have traditionally acquired, organized, and disseminated scholarly information. Therefore, it has been a logical step that institutional libraries would take the lead in managing research output through repositories (Horwood, 2004). An Australian study by Henty (2007) revealed that "the open access origin of many repositories has led to responsibility for the repository being held by the library in all but one of the universities surveyed."…”
Section: Literature Reviewmentioning
confidence: 99%
“…Academic library staff have traditionally acquired, organized, and disseminated scholarly information. Therefore, it has been a logical step that institutional libraries would take the lead in managing research output through repositories (Horwood, 2004). An Australian study by Henty (2007) revealed that "the open access origin of many repositories has led to responsibility for the repository being held by the library in all but one of the universities surveyed."…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been suggested that the establishment of IR should be the role of the library as it complements the already established roles of libraries in providing access to scholarly material and information management (Bosc and Harnad, 2005;Horwood, et al, 2003), and indeed in many organisations this is so. In some cases repositories are restricted to research output, and in others they include other intellectual capital that belongs to the institution, such as teaching and learning materials (Horwood, et al, 2003).…”
Section: Irandlmmentioning
confidence: 99%
“…In some cases repositories are restricted to research output, and in others they include other intellectual capital that belongs to the institution, such as teaching and learning materials (Horwood, et al, 2003).…”
Section: Irandlmmentioning
confidence: 99%
“…Thus, libraries' changing role is to participate in scholarly communication by supporting electronic scholarly knowledge products and also provide and organise digital content through institutional repositories. There is evidence, for example, in Australia (Horwood et al 2004) and also in South Africa, where such initiatives focusing on the role of libraries in the development of institutional repositories and the benefits arising from the changing functions of libraries (including technical requirements) are represented. OAI has many advantages stemming from its ability to increase relevancy, use, recognition, advocacy and promotion, accountability, visibility (Onyancha 2007a) and access in modern times.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%